SIPEMANDU-GPT: A DIGITAL TRAINING MODEL FOR 21ST CENTURY PE TEACHER PROFESSIONALISM - Rozi, Fatkhur; Priyono, Bambang; Putro, Baskoro Nugroho; Ratimiasih, Yulia; Prastiwi, Bertika Kusuma; Indarto, Pungki (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to develop a technology-based training design for physical education teachers through the Sipemandu-GPT model to enhance teacher professionalism.Methodology – This study employed a research and development (R&D) approach, adapting the Borg & Gall development model. The initial stage began with a preliminary study through interviews and observations involving KKGOMI teachers in Jepara Regency. The findings revealed that the training previously received was monotonous, lacked contextual relevance, and had not integrated technology. Consequently, a prototype training model based on blended learning was developed, combining online components (interactive modules, tutorial videos, virtual discussion forums) and offline components (teaching simulations, group discussions, written reflections).Findings – Validation by three experts indicated that the training design fell within the "valid" to "highly valid" category, with several improvement notes, such as adding visual flowcharts and providing worksheets. After revisions, a limited trial was conducted involving 14 teachers. The results showed an increase in average scores from the pre-test (55.6) to the post-test (84.5), with an average improvement of 28.9 points. These findings suggest that the Sipemandu-GPT-based training effectively enhances the competence and professionalism of physical education teachers.Contribution – Providing a flexible and contextual technology-based training model to support teachers’ professional development, particularly in responding to the demands of the Kurikulum Merdeka and the digital transformation of education.